Mechanics and regulation of cytokinetic abscission - Andrade, Virginia; Echard, Arnaud (Frontiers in Cell and Developmental Biology, 2022)
Cytokinetic abscission leads to the physical cut of the intercellular bridge (ICB) connecting the daughter cells and concludes cell division. In different animal cells, it is well established that the ESCRT-III machinery is responsible for the constriction and scission of the ICB. Here, we review the mechanical context of abscission. We first summarize the evidence that the ICB is initially under high tension and explain why, paradoxically, this can inhibit abscission in epithelial cells by impacting on ESCRT-III assembly. We next detail the different mechanisms that have been recently identified to release ICB tension and trigger abscission. Finally, we discuss whether traction-induced mechanical cell rupture could represent an ancient alternative mechanism of abscission and suggest future research avenues to further understand the role of mechanics in regulating abscission.